Progesterone Receptor B Promoter Hypermethylation in Human Placenta After Labor Onset. (March 2015) - Zhuang, Yanyan; Cui, Hong; Liu, Sishi; Zheng, Dongming; Liu, Caixia
To determine the methylation status of progesterone receptor B (PR-B) promoter and how PR-B regulates progesterone action in placenta during human pregnancy. Placentas were obtained from the pregnancy women at term who underwent cesarean delivery and vaginal delivery. The methylation status of the PR-B promoter was analyzed using the methylation-specific polymerase chain reaction (PCR) and bisulfite sequencing PCR. And the messenger RNA (mRNA) and protein expression of the PR-B and DNA methyltransferases (DNMTs) were determined by quantitative real-time PCR and Western blot. Compared with the cesarean group, the placentas of vaginal delivery group had greater levels of PR-B DNA methylation, and the PR-B, DNMT1, DNMT3a, and DNMT3b mRNA and protein expression were significantly decreased. Progesterone receptor B methylation occurs with high frequency after labor onset and may play an important epigenetic mechanism of labor-related PR-B negative expression, thereby mediating the biological process of functional progesterone withdrawal at term for parturition.